The effectiveness of physical exercise in patients with lumbar spinal stenosis: a systematic review - SARI, ZÜBEYİR (My University, 2022)
Background To our knowledge, no other systematic review comprehensively demonstrated the effectiveness of exercise and conventional physiotherapy in lumbar spinal stenosis (LSS). Aims The purpose of the present systematic review was to provide a comprehensive review of exercise therapy on LSS. Methods A literature search was carried out in the following databases on October 2021: PubMed, Scopus, ScienceDirect, Cochrane Library, and Web of Science (WoS) database. The study quality assessment was independently determined according to the PEDro scores by two reviewers. A narrative synthesis was used to synthesize the data of the compiled studies and express their results. Results Records identified through database searching; PubMed (n = 352), Web of Science (n = 180), Science Direct (n = 2801), Cochrane Library (n = 423) and Scopus (n = 12). A total of 3768 papers were screened. Studies unrelated to the question, another study language, undesired study design, duplicate articles, undesired intervention, undesired sample feature (n = 3757) were excluded. An analysis was conducted on the full text of 11 journals. The vast majority (90.9%) of articles received a PEDro score of 6-8 (\"good\"). The mean PEDro score of the studies was 6.8 +/- 1.5 (min:1, max:8). Four of the studies (36.3%) focused on neurogenic claudication in the LSS. Other studies have focused on LSS due to various causes (e.g., degenerative). Conclusions The review results showed that supervised exercise was more effective in LSS than self-management or home exercise. In addition, core stabilization, aqua therapy or aerobic (e.g., treadmill, cycling) exercises can be advantageous in different parameters.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; SPOR BİLİMLERİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SPORT SCIENCES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); General Social Sciences; Social Sciences & Humanities; Exercise; Physiotherapy; Stenosis; Review; NONSURGICAL TREATMENT; SURGERY; THERAPY